A budget impact analysis of budesonide/formoterol in patients with mild asthma in Egypt. (3rd October 2019) - Elsisi, Gihan Hamdy; Carapinha, João; Amin, Wagdy; Thabet, Ehab; Elafify, Safaa; Amin, Mohamad; Hatem, Ashraf
Abstract: Background: The aim of this study is to estimate the budget impact of budesonide/formoterol fixed dose combination (FDC) vs salbutamol, both used as needed, in mild asthma patients, from the perspective of the Health Insurance Organization (HIO). Methods: A static budget impact model was developed to assess the impact of budesonide/formoterol FDC entry on HIO budget over a 3-year period in Egyptian settings. Direct medical costs, including the costs of asthma medications, exacerbations, and management of side-effects, were obtained from HIO cost data. Population data were obtained from the World Bank and supplemented with local studies, and the rates of exacerbations, adverse effects, and number of sick leave days were elicited from the SYGMA 1 trial. Scenario analyses from a societal perspective and deterministic sensitivity analyses were conducted. Results: The total costs (drug and non-drug costs) for managing mild asthma patients from the HIO perspective were estimated to be EGP8.563 billion before budesonide/formoterol entry compared to EGP5.525 billion post-entry, leading to a total budget savings of EGP3.038 billion after 3 years. This total budget saving included an increase in drug costs (EGP104 million) and a decrease in non-drug costs (EGP3.143 billion). Drug costs were higher in the budesonide/formoterol group than in the salbutamol group, but this cost was offset by reductions in non-drug costs, resulting in a reduction in the total costs of healthcare resources. At the societal level, the total budget savings after including the indirect costs was expected to be EGP5.976 billion after 3 years of budesonide/formoterol entry. Conclusion: Budesonide/formoterol in mild asthma instead of salbutamol produces better patient outcomes and decreases total costs, with increases in drug cost offset by reductions in non-drug costs due to fewer exacerbations. Budesonide/formoterol is a budget saving option for guideline-directed treatment, from the economic perspective of the payer and the health perspective of the patient.